English Vowel Pronunciation Errors among Vocational High School Students - Nurlaila; Andi Rachmawati Syarif; Muflihun (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study identifies and classifies English vowel pronunciation errors produced by eleventh-grade students at SMK Negeri 1 Kendari while reading English words aloud. A descriptive qualitative approach, supported by frequency-based summaries, was employed. The participants were 20 students from Class XI Office Major 4. Data were collected in two pronunciation-test sessions using a predetermined list of English words representing short vowels, long vowels, and diphthongs. Students' productions were audio-recorded, transcribed with an MP3-to-IPA transcription tool, and compared with reference pronunciations in the Oxford Advanced Learner's Dictionary. The original coding classified the data as substitution, addition, or omission following Crystal's (2008) framework. The analysis yielded 106 coded vowel-error instances: 94 substitutions, 9 additions, and 3 omissions. Substitution was therefore the most frequent category. Recurring difficulties were also observed in words containing diphthongs, while addition commonly involved vowel insertion and omission involved the deletion of weak vowels. These patterns may be associated with differences between learners' familiar sound system and English pronunciation, although the study did not directly investigate causal factors. The findings support the need for explicit pronunciation instruction, repeated listening and production practice, and systematic feedback on English vowel contrasts in vocational high school classrooms.